2021
DOI: 10.1111/cyt.13053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic impact of safety protocols for processing peritoneal washing specimens during the global pandemic of coronavirus disease 2019: A comparative study from 195 cytological samples

Abstract: Background Global pandemic of Coronavirus disease 2019 represented a major concern for the health services worldwide, also determining major changes in cytopathology practice. Aim We aimed to establish the diagnostic performance of cytologic evaluation with the new safety protocol to process cytological samples compared to the standard one. We also aimed to assess how cytological diagnoses and sampling were impacted during the pandemic period compared to the pandemic‐fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The estimated ROM for each category was: ND, 0%-57.1%; NFM, Eleven studies provide data for peritoneal effusions, and ROM was assessed in seven of them (Table 3). 18,[20][21][22][24][25][26]29,31,35,36 The number of samples/patients ranged from 217 to 2257 in studies with reported ROM. The estimated ROM for each category was: ND, 0%-100%; NFM, 1.8%-27.5%; AUS, 22.2%-62.5%; SFM, 80%-100%; MAL, 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated ROM for each category was: ND, 0%-57.1%; NFM, Eleven studies provide data for peritoneal effusions, and ROM was assessed in seven of them (Table 3). 18,[20][21][22][24][25][26]29,31,35,36 The number of samples/patients ranged from 217 to 2257 in studies with reported ROM. The estimated ROM for each category was: ND, 0%-100%; NFM, 1.8%-27.5%; AUS, 22.2%-62.5%; SFM, 80%-100%; MAL, 100%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies mentioned before, data regarding peritoneal washings cytology according to the TIS are presented by Santoro et al 35 without ROM evaluation, as this study mainly addressed the impact of Covid on the performance of a cytology lab. Peritoneal washings from patients with endometrial cancer without application of the TIS have also been discussed by Davis et al 40 The authors concluded that the cytology of peritoneal washings is a reliable diagnostic method with good performance and high reproducibility, even without application of the TIS criteria.…”
Section: Discussionmentioning
confidence: 99%